2009
DOI: 10.1089/ast.2006.0117
|View full text |Cite
|
Sign up to set email alerts
|

Organics Produced by Irradiation of Frozen and Liquid HCN Solutions: Implications for Chemical Evolution Studies

Abstract: Hydrogen cyanide (HCN), an important precursor of organic compounds, is widely present in extraterrestrial environments. HCN is also readily synthesized in prebiotic simulation experiments. To gain insight into the radiation chemistry of one of the most important and highly versatile constituents of cometary ices, we examined the behavior of over-irradiated frozen and liquid HCN solutions under ionizing radiation. The samples were exposed to gamma radiation at a dose range from 0 up to 419 kGy. Ultraviolet spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…A series of experiments employing the irradiation of various starting compounds, including HCN, were shown to produce some compounds also found in meteorites (19,20). The list includes some of the compounds we report here such as tricarballyic acid and citric acid (20). Tricarballyic acid (and other tricarboxylic acids) is also produced by aqueous reactions of pyruvate (outlined below).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…A series of experiments employing the irradiation of various starting compounds, including HCN, were shown to produce some compounds also found in meteorites (19,20). The list includes some of the compounds we report here such as tricarballyic acid and citric acid (20). Tricarballyic acid (and other tricarboxylic acids) is also produced by aqueous reactions of pyruvate (outlined below).…”
mentioning
confidence: 92%
“…The exposure of interstellar grains and comets to various forms of radiation inspired research into how such phenomena would affect the production of organic compounds (19). A series of experiments employing the irradiation of various starting compounds, including HCN, were shown to produce some compounds also found in meteorites (19,20). The list includes some of the compounds we report here such as tricarballyic acid and citric acid (20).…”
mentioning
confidence: 96%
“…In addition, the irradiation with protons [5], beta rays [6], and X rays [7] yield urea from a mixtures of gases (methane, ammonia, and water). It is also easily synthesized from the irradiation of hydrogen cyanide (HCN) in a liquid or solid state [8]. Additionally, it has been suggested that the participation of urea in different reactions could have favored the synthesis of more complex organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of chemical evolution [68], irradiated propane and methane or carbon monoxide with high energy protons in the presence of water and ammonia, after an acid hydrolysis, detected the formation of amino acids. The behavior of over-irradiated frozen HCN solutions has been studied by Colin-Garcia et al [69,70]. Their analysis confirmed that gamma-ray irradiation generates several organic products, among them carboxylic acids, amino acids, and urea, all of which have biological relevance.…”
Section: Experiments In Icesmentioning
confidence: 97%